Ischemia-reperfusion-induced delay in intestinal transit - Role of endothelins - YEGEN, BERRAK (KARGER, 1998)
Background/Aims: To evaluate the involvement of ET-1 in ischemia-reperfusion (I/R) injury. Methods: Superior artery occlusion was performed in Wistar albino rats for 30 min followed by 2-hour (early reperfusion; ER) or 24-hour (late reperfusion; LR) reperfusion periods. Results: Intestinal transit was found to be reduced in the ER and LR groups (19.0 +/- 2.5%; p < 0.001 and 72.7 +/- 6.0%; p < 0.05, respectively) compared to the control group (85.8 +/- 2.5%), while treatment with the ET receptor antagonist bosentan (BOS; 10 mg/kg i.v.) abolished this delay in LR. Myeloperoxidase activity showed a significant increase in ER(7.07 +/- 85.70 U/g; p < 0.001) compared to control (281.16 +/- 43.23 U/g), but BOS had no effect on this increase. The protein oxidation level was found to be higher in LR(5.92 +/- 0.77 nmol/mg protein; p < 0.05) compared to the control (3.77 +/- 0.45 nmol/mg protein), and was reversed by BOS treatment. Conclusion: The results of the present study imply that I/R delays intestinal transit involving an endothelin-dependent mechanism.
Keywords: endothelin; bosentan; ischemia-reperfusion; neutrophil; intestinal transit; protein oxidation; myeloperoxidase activity; MYOCARDIAL-ISCHEMIA; INJURY; DYSFUNCTION; MOTILITY; NEUTROPHILS; SUPEROXIDE; ADHESION; TISSUES; HEART; RAT